2005
DOI: 10.1073/pnas.0503252102
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phylogenomics of the food-borne pathogen Campylobacter jejuni reveals genetic markers predictive of infection source

Abstract: Campylobacter jejuni is the predominant cause of bacterial gastroenteritis worldwide, but traditional typing methods are unable to discriminate strains from different sources that cause disease in humans. We report the use of genomotyping (whole-genome comparisons of microbes using DNA microarrays) combined with Bayesian-based algorithms to model the phylogeny of this major food-borne pathogen. In this study 111 C. jejuni strains were examined by genomotyping isolates from humans with a spectrum of C. jejuni-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
156
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(163 citation statements)
references
References 28 publications
3
156
1
3
Order By: Relevance
“…Campylobacter isolates display significant genetic diversity within this locus, which has been shown to be responsible for the antigenically distinct PseAm glycan variants produced by individual strains (Logan et al, 2002). Most recently, comparative phylogenomics revealed a cluster of six genes within this locus to be a specific marker for a 'livestock' clade (Champion et al, 2005), although the role of these genes in production of a unique glycoform relevant to adhesion in the livestock gut has yet to be demonstrated. The annotation of the locus suggested that approximately 50 % of the genes were likely to be involved in carbohydrate biosynthetic pathways and that some of them had homology to sialic acid biosynthesis genes (neuA, neuB, neuC).…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…Campylobacter isolates display significant genetic diversity within this locus, which has been shown to be responsible for the antigenically distinct PseAm glycan variants produced by individual strains (Logan et al, 2002). Most recently, comparative phylogenomics revealed a cluster of six genes within this locus to be a specific marker for a 'livestock' clade (Champion et al, 2005), although the role of these genes in production of a unique glycoform relevant to adhesion in the livestock gut has yet to be demonstrated. The annotation of the locus suggested that approximately 50 % of the genes were likely to be involved in carbohydrate biosynthetic pathways and that some of them had homology to sialic acid biosynthesis genes (neuA, neuB, neuC).…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…The absence of an association between the presence of pVir and bloody stools suggests that other virulence factors may be involved in the development of bloody diarrhea. A suggestion in this direction was recently made by Champion et al (2), who proposed a serine protease encoded by Cj1365 as a virulence factor involved in the development of bloody diarrhea. Previously, serine proteases have been described in Enterobacteriaceae and are thought to be involved in the development of bloody diarrhea caused by Escherichia coli (4).…”
mentioning
confidence: 99%
“…Some systems display robust inter-and intrastrain glycan variability, suggesting that glycoform diversification is adaptive. For example, flagellar protein glycosylation systems in Campylobacter jejuni and Clostridium species display remarkable plasticity in glycoform expression (2)(3)(4). However, precise correlations between glycosylation gene content and glycoform phenotypes have been difficult to establish.…”
mentioning
confidence: 99%